The grotesque in the fiction of Charles Dickens and other 19th-century European novelists - Hervouet-Farrar, Isabelle; Véga-Ritter, Max (Cambridge Scholars Publishing, 2014)
This book provides an overview of the literary grotesque in 19th-century Europe, with special emphasis on Charles Dickens, whose use of this complex aesthetic category is thus addressed in relation with other 19th-century European writers. The crossing of geographical boundaries allows an in-depth study of the different modes of the grotesque found in 19th-century fiction. It provides a comprehensive analysis of the reasons behind the extensive use of such a favoured mode of expression. Intertextuality and comparative or cultural analysis are thus used here to shed new light on Dickens's influ.